MOLECULAR GENETIC TESTING OF ACCP-POSITIVE PATIENTS WITH RHEUMATOID ARTHRITIS AND HIGH INFLAMMATORY DISEASE ACTIVITY (A REMARCA STUDY) - I. A. Guseva; E. L. Luchikhina; N. V. Demidova; A. S. Avdeeva; N. E. Soroka; D. D. Abramov; M. V. Cherkasova; E. Yu. Samarkina; D. E. Karateev; E. L. Nasonov (Научно-практическая ревматология)
Rheumatoid arthritis (RA) is a multifactorial disease, in which the interaction of the genetic component and environmental factors, determines not only the development of the disease, but also its pronounced clinical polymorphism. We assume that the high inflammatory activity of RA may be determined by the genes, the products of which trigger inflammatory processes.Objective: to investigate allele and genotype distribution of gene polymorphic variants in active anti-cyclic citrullinated peptide (aCCP)-positive patients with RA from the REMARCA program versus a control group of healthy blood donors.Subjects and methods. A molecular genetic study enrolled 146 aCCP-positive patients from the REMARCA program and a control group of 314 healthy blood donors without autoimmune diseases and their presence in the history, who were matched with the study group for gender and sex. The polymorphic variants of the genes PTPN22 (+1858C>T, rs2476601), TNFAIP3 (rs6920220, rs10499194), CTLA4 (+49A>G, rs231775), TNFА (-308A>G, rs1800629), IL6 (-174G>C, rs1800795), IL6R (+358A>C, rs8192284), IL10 (-592A>C, rs1800872, -892 C>T, rs1800871, -1082 A>G, rs1800896), and MCP1/CCL2 (+2518A>G, rs1024611) were genotyped by a real-time polymerase chain reaction assay.Results and discussion. The genotype and allele frequencies of polymorphic variants of the genes CTLA4 (+49A>G), IL-6R (+358A>C), and IL10 (592A>C) in the RA group significantly differed from those in the control group. When comparing with the control group, the minor alleles of the CTLA4 and IL10 genes were markers for the risk of aCCP-positive RA with a high inflammatory activity (OR=1.4 [1.1; 1.9], p=0.02 and OR=1.9 [1.4; 2.5]; p=0.0001, respectively). At the same time, the minor C allele of the IL6R gene served as a marker of protection (OR=0.7 [0.5; 0.9]; p=0.03). Logistic regression analysis revealed that there was a statistically significant correlation of the high inflammatory activity indices SDAI, CDAI, and DAS28 with the minor homozygous GG genotype of the CTLA4 gene (OR=2.5 [1.1; 6.0]; p=0.03, OR=2.6 [1.1–6.4], p=0.03 and OR=3.4 [1.3–8.8]; p=0.01, respectively). In addition, the inflammatory activity indices SDAI and CDAI rather than DAS28-ESR were associated with at least one minor A allele (the AA/AC genotypes) of the IL10 gene (OR=2.4 [1.2; 5.1], p=0.02 and OR=2.2 [1.1; 4.7]; p=0.03, respectively). The levels of ESR and CRP were not associated with the examined polymorphisms.Conclusion. The findings may suggest that there is a relationship of the polymorphisms of the genes CTLA4 (+49A>G, rs231775), IL6R (+358A>C, rs8192284), and IL10 (-592A>C, rs1800872) to high inflammatory activity in the group of aCCP-positive patients from the REMARCA study.